Determinants of Capital Structure Policy at Indonesian Sharia Bank Demang Palembang Branch - Fadilla Fadilla; lidya pissatia asih (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2022)
The perpose of this study to aim influece of ROA (return on Asset), ROE (return on equity) dan DER (Debt to equity ratio) to DR (Debt ratio) in Sharia Islamic Banking Demang Lebar Daun Palembang. Analysis of data using multiple regression analysis tools. The result of this study ROA, ROE and DER simultaneosly effect the Debt ratio, but there are no partialy effect ROA dan ROE to Debt ratio, and DER have partialy effect to debt ratio. This study focus on ROA, ROE, DER and Debt ratio. This study usefeul further reseach to discuss about capital structure. Key word : ROA (return on Asset), ROE (return on equity), DER (Debt to equity ratio) to DR (Debt ratio)